A novel kefir product (PFT) inhibits Ehrlich ascites carcinoma in mice via induction of apoptosis and immunomodulation* - Nariman K. Badr El-Din; Sameh M. Shabana; Bashar A. Abdulmajeed; Mamdooh Ghoneum (BMC, 2020)
Abstract Background The popularity of fermented foods such as kefir, kuniss, and tofu has been greatly increasing over the past several decades, and the ability of probiotic bacteria to exert anticancer effects has recently become the focus of research. While we have recently demonstrated the ability of the novel kefir product PFT (Probiotics Fermentation Technology) to exert anticancer effects in vitro, here we demonstrate its ability to inhibit Ehrlich ascites carcinoma (EAC) in mice. Methods Mice were inoculated intramuscularly with EAC cells to develop solid tumors. PFT was administered orally (2 g/kg/day) to mice 6 days/week, either 2 days before tumor cell inoculation or 9 days after inoculation to mice bearing solid tumors. Tumor growth, blood lymphocyte levels, cell cycle progression, apoptosis, apoptotic regulator expression, TNF-α expression, changes in mitochondrial membrane potential (MMP), PCNA, and CD4+ and CD8+ T cells in tumor cells were quantitatively evaluated by flow cytometry or RT-PCR. Further studies in vitro were carried out where EAC cells along with several other human cancer cell lines were cultured in the presence of PFT (0-5 mg/mL). Percent cell viability and IC50 was estimated by MTT assay. Results Our data shows that PFT exerts the following: 1) inhibition of tumor incidence and tumor growth; 2) inhibition of cellular proliferation via a marked decrease in the expression of tumor marker PCNA; 3) arrest of the tumor cell cycle in the sub-G0/G1 phase, signifying apoptosis; 4) induction of apoptosis in cancer cells via a mitochondrial-dependent pathway as indicated by the up-regulation of p53 expression, increased Bax/Bcl-2 ratio, decrease in the polarization of MMP, and caspase-3 activation; and 5) immunomodulation with an increase in the number of infiltrating CD4+ and CD8+ T cells and an enhancement of TNF-α expression within the tumor. Conclusions PFT reduces tumor incidence and tumor growth in mice with EAC by inducing apoptosis in EAC cells via the mitochondrial-dependent pathway, suppressing cancer cell proliferation, and stimulating the immune system. PFT may be a useful agent for cancer prevention.